The Role of Vitamin D in the Relationship Between Gender and Deep Vein Thrombosis Among Stroke Patients - Tao, Jiejie; Lou, Feiling; Liu, Yuntao (Frontiers in Nutrition, 2021)
Abstract INTRODUCTION: Accumulating evidence had demonstrated that females had a higher risk of deep vein thrombosis (DVT) than males, but the mechanism was still unknown. Vitamin D was found to play an essential role in DVT, and gender may influence the serum vitamin D levels. This study aimed to explore whether vitamin D played a role in the gender difference in DVT. MATERIALS AND METHODS: A total of 444 patients with acute stroke were recruited, which were divided into the DVT group (n = 222) and the non-DVT group (n = 222). Serum vitamin D levels were measured after admission and were split into three categories, including deficiency (less than 50 nmol/L), insufficiency (52.5–72.5 nmol/L), and sufficiency (more than 75 nmol/L). Hierarchical regression analysis was adopted to analyze the relationship between gender and DVT, controlling the confounding factors. RESULTS: Females showed a higher proportion of DVT than males (60.7% vs. 42.5%, p < 0.001), and lower serum vitamin D levels than males (53.44 ± 16.45 vs. 69.43 ± 23.14, p < 0.001). Moreover, serum vitamin D levels were lower in the DVT group than in the non-DVT group (59.44 ± 19.61 vs. 66.24 ± 23.86, p < 0.001). Besides, the DVT group showed a lower proportion of vitamin D sufficiency than the non-DVT group (21.2% vs. 32.9%, p < 0.05). Hierarchical regression analysis showed that females had 2.083-fold (p < 0.001, unadjusted model) and 1.413-fold (p = 0.155, adjusted model) risk to develop DVT. In addition, the sufficiency status of vitamin D showed an independent protective effect on DVT (unadjusted model OR, 0.504, p = 0.004; adjusted model OR, 0.686, p = 0.011). CONCLUSION: Females had a higher risk of DVT than males, and vitamin D may play an essential role in this relationship. Further studies are needed to explore whether vitamin D supplementation could reduce DVT risk in stroke patients, especially females.